From photoperiod thresholds to photoperiod sensitivity: dual strategies for cost-effective speed breeding and climate-ready barley - Rossi, Nicola; Powell, Wayne; Halliday, Karen; Sharma, Rajiv (Frontiers in Plant Science, 2026)
IntroductionSpeed breeding (SB), characterized by extended photoperiods to accelerate generation time, can be energy-intensive, and the minimum day length required to trigger rapid flowering remains unknown. Additionally, climate change raises the need for shorter growing seasons in certain European regions, and reducing the time to flowering could be an effective strategy to mitigate its effects. Therefore, exploring how allelic combinations shape flowering time is needed. We present the first integrated study of how allelic variation at three key flowering time genes —PPD-H1, ELF3, and PHYC — modulates three parameters of the photoperiod response model: threshold photoperiod, photoperiod sensitivity, and intrinsic earliness.Materials and methodsWe recorded flowering under lengths of 16–24h in Near Isogenic Lines carrying PhyC-e or PhyC-I allele within ppd-H1 background, and in lines from HEB-25 combining wild and domesticated alleles of ELF3 and PPD-H1.Results and discussionRemarkably, ppd-H1 lines flowered at a 20-h threshold, whereas Ppd-H1 lines showed no response, consequently we propose new SB photoperiods at 20 and 16h depending on PPD-H1 background. These photoperiods lower energy costs compared to the current 22h standard. In addition, the wild ELF3 allele in ppd-H1 background reduced intrinsic earliness, whereas PhyC-e reduced photoperiod sensitivity, opening opportunities for climate change adaptation.